2008
DOI: 10.1108/01443330810915251
|View full text |Cite
|
Sign up to set email alerts
|

Islamophobia: examining causal links between the media and “race hate” from “below”

Abstract: Purpose -The paper's aim is to examine whether there is a causal link between ''race'' hate, particularly Islamophobia (defined as anti-Muslim feeling and violence based on ''race'' and/or religion), and media treatment of Muslim communities in Britain in recent years. Design/methodology/approach -The paper looks at the reporting of terror activities and examines the way the media (tabloid press) constructs racists news. Findings -The article discusses some of the themes developed in a previous paper that look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…86 In particular, the media has played a very important role in the negative stereotyping and criminalisation of Muslims. 87 The demonisation of Muslims in the popular imaginaries could construct what Cohen 88 would call "folk devils" or suitable enemies in a post-modern realm, where British society at large personifies that suitable victim whose ideological Britishness, which is grounded on monocultural whiteness and identity securitisation from the threat of the social other, is to be preserved. The emergence of widespread moral panics 89 risk shaping a collective conscience grounded on absolutist ontological boundaries that perpetuate Islamophobia and further mould fifth column discourses around Muslim communities.…”
Section: Demonising Muslims At First Sightmentioning
confidence: 99%
“…86 In particular, the media has played a very important role in the negative stereotyping and criminalisation of Muslims. 87 The demonisation of Muslims in the popular imaginaries could construct what Cohen 88 would call "folk devils" or suitable enemies in a post-modern realm, where British society at large personifies that suitable victim whose ideological Britishness, which is grounded on monocultural whiteness and identity securitisation from the threat of the social other, is to be preserved. The emergence of widespread moral panics 89 risk shaping a collective conscience grounded on absolutist ontological boundaries that perpetuate Islamophobia and further mould fifth column discourses around Muslim communities.…”
Section: Demonising Muslims At First Sightmentioning
confidence: 99%
“…A study by Featherstone, Holohan, and Poole (2010) found that four major British newspapers reflected an implicit blame against British Muslims after the July 2005 London bombings for "their blindness and naivety to what had been going on in their own communities" (Featherstone, Holohan, and Poole 2010, 178). Frost (2008) found that the British press adopted a campaign of "moral panic" that normalized hatred against British Muslims after the July 2005 bombings (Frost 2008, 574).…”
Section: Literature Review: Terrorism and Islam In Western Mediamentioning
confidence: 99%
“…In some states in Australia, despite mandatory enforcement, only 21 of the 40 schools had participated in such reforms (Szoke 2012;Syed and Kramar 2010). In ethnically divided communities, the government plays a major role at the national level to continuously evolve with macro-national level strategies (Mansouri et al 2012;Frost 2008). Even leaders could take up individual initiatives to repair any harm made by their predecessors.…”
Section: Education System Framework To Address Racismmentioning
confidence: 99%